The Analysis of Bale Banjar Shifted Function: Socio-Cultural and Economy Implications in Kuta, Bali - Mahastuti, Ni Made Mitha; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin; Susanta, I Nyoman (Universitas Ibn Khaldun Bogor, 2025)
This research analyzes the shift in the function of bale banjar in Kuta District, Bali, in the context of modern tourism development. This shift in function includes a transformation from a center for social and cultural activities into a commercial and multifunctional space. This research also examines the socio-cultural and economic implications of these changes. Data was obtained through qualitative methods with in-depth interviews, observation and documentation studies. The research results show that modern tourism has a significant impact on changes in the function and form of bale banjar, as well as changing the social and economic dynamics of local communities. These changes affect traditional cultural values ​​and the social identity of communities, necessitating appropriate conservation and adaptation strategies to maintain a balance between tourism development and preservation of traditional values. This research provides an important contribution in understanding the dynamics of bale banjar transformation and its implications for Balinese society in the modern tourism era.